Production and Marketing Practice of Maize in North Coastal Andhra Pradesh (Indian Journal of Extension Education, 2024)
The results of the research conducted during the 2023-24 period offer significant insights into the production and marketing practices of maize farmers in the Srikakulam and Vizianagaram districts of Andhra Pradesh. This distribution indicates that the majority of growers are moderately engaged in marketing activities, with a notable proportion demonstrating high engagement. The proportion of variability in the dependent variable that is explained by the independent variables was 0.775 suggesting that the 15 variables selected in the study account for a significant 77.5 per cent of the variability in the marketing behavior of these maize growers. This strong predictive value underscores the importance of the identified factors in influencing marketing practices. These insights can be instrumental in tailoring interventions and training programs to enhance the marketing skills of maize growers, ultimately contributing to better market integration and increased profitability.